PENGARUH AKUNTABILITAS DAN TRANSPARANSI PEMERINTAH DESA TERHADAP PENGELOLAAN DANA DESA: Studi Kasus Desa Turus Kecamatan Kemiri Kabupaten Purworejo - Kerod Turiman (Prospect : Jurnal Manajemen dan Akuntansi, 2022)
The principles of transparency and accountability must be upheld in the management of village funds. Second, as a key in implementing the program planned by the village government and ensuring that the amount of funds is allocated properly. This researcher entitled The Effect of Government Accountability and Transparency on Village Fund Management (Case Study Turus Village, Kemiri District, Purworejo Regency. The main purpose of this research is that the researcher wants to examine more deeply about the management of the Village Fund, especially in the village of Turus.Sources of data using primary and secondary data.The population in this study is the people who live in Turus Village.The sampling technique used is the purposive sampling technique, with a total of 80 samples.Instrument testing techniques include validity and reliability tests. The data analysis technique used is the classical assumption test in the form of: 1) normality, 2) multicollinearity, 3) heteroscedasticity. Hypothesis testing using multiple linear regression analysis coefficient of determination, t test and F test. The results show that 1) the regression coefficient (β) of Accountability (X1) on the management of village funds (Y) is 0.245 with a significant value of 0.008 (p value <0.05), which means that the Accountability variable has an effect on the management of Village Funds. 2) The test results show the regression coefficient value (β) of Transparency (X2) to the management of village funds (Y) of 0.588 with a significant value of 0.000 (p value <0.05), which means that variable transparency partially affects the management of Village Funds. 3) The value of sig p is 0.00, because the value of sig. p < 0.05, it can be interpreted that there is a simultaneous influence between the accountability variable and the transparency variable on the management of village funds. then it is known that F count = 36.467 which means that the variables of accountability andtransparency simultaneously affects the management of village funds. 4) The result of the coefficient of determination shows 0.486. It can be interpreted that the transparency and transparency variables simultaneously are 48.6%, while the variables outside the measured are (100%-48.6%) = 51.4%.